Mutation screening analysis of the retinoblastoma related gene RB2/p130 in sporadic ovarian cancer and head and neck squamous cell cancer. Issue 3 (1st June 2002) - Alvi, A J; Hogg, R; Rader, J S; Kuo, M J; Maher, E R; Latif, F
Abstract : Aims: To investigate the involvement of the RB2/p130 gene in the pathogenesis of sporadic ovarian cancer in addition to head and neck squamous cell carcinoma (HNSCC). Methods: Paired tumour and patient matched normal DNA samples from 43 sporadic ovarian tumours and 39 normal/tumour HNSCC DNA samples were screened. The mutation screen used polymerase chain reaction (PCR) amplification followed by single strand conformation polymorphism analysis and direct sequencing of the PCR products. Exons 19 and 20 (B domain) and exons 21 and 22 (C-terminus) were analysed for mutations. These exons were chosen because most of the point mutations in RB2/p130 are located in the C-terminal region and mutations in these exons have been identified previously in nasopharyngeal carcinomas and primary lung tumours. Results: No abnormal band shifts were seen in the samples analysed, and no bands directly sequenced revealed the presence of mutations. Conclusions: Genetic alterations in the RB2/p130 gene (exons 19–22) are unlikely to be involved directly in the pathogenesis of sporadic ovarian cancer or HNSCC.